2016
DOI: 10.18632/oncotarget.10559
|View full text |Cite
|
Sign up to set email alerts
|

MET amplification in metastatic colorectal cancer: an acquired response to EGFR inhibition, not a de novo phenomenon

Abstract: BackgroundMET amplification appears to be a predictive biomarker for MET inhibition. Prior studies reported a MET amplification rate of 9–18% in metastatic colorectal cancer (mCRC) but do not differentiate increased gene copy numbers due to chromosomal level aberrations from focal gene amplifications. Validation of MET amplification rate in mCRC is critical to this field.ResultsIn tumor tissue-based analyses, overall MET amplification rate was 1.7% (10/590). MET amplification was seen in 0/103 (0%), 4/208 (1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 19 publications
2
46
1
Order By: Relevance
“…Subsequent to completion of our study, the cfDNA test has become comprehensive (i.e. inclusive of all four major types of alterations), which will likely become important as new genomic targets such as RSPO3 and other fusions, or ERBB2 (HER2) and MET gene copy number amplifications, may become potential targets on the near horizon [ 5 , 40 , 41 ]. Findings from sequencing of cfDNA can inform the provider of matched biomarker-based clinical trials while also improving the perceived quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to completion of our study, the cfDNA test has become comprehensive (i.e. inclusive of all four major types of alterations), which will likely become important as new genomic targets such as RSPO3 and other fusions, or ERBB2 (HER2) and MET gene copy number amplifications, may become potential targets on the near horizon [ 5 , 40 , 41 ]. Findings from sequencing of cfDNA can inform the provider of matched biomarker-based clinical trials while also improving the perceived quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned use of MET dysregulation for biomarker discovery in tumor tissue, recently a promising noninvasive method based on the detection of circulating tumor DNA (ctDNA) in blood samples has also been suggested as a cancer biomarker [237][238][239][240][241][242][243]. One study comparing the MET amplification rate in different tissue-based and blood-based analysis methods showed that the frequency of MET amplification using ctDNA in metastatic colorectal cancer patients after exposure to anti-EGFR antibody therapy was significantly increased compared with antibodynaïve patients (p < .001) [237]. Similarly, a case report of a treatment refractory patient with metastatic colorectal cancer showed that MET amplification was detected in ctDNA using next-generation sequencing, but not in tissue biopsy samples.…”
Section: Vi-b-circulating Tumor Dnamentioning
confidence: 99%
“…Cotreatment with MET inhibitors and cetuximab caused robust and longlasting tumor shrinkage in patient-derived xenograft models of MET-amplified mCRC. In a study investigating the frequency of MET amplification in a large cohort of patients with mCRC, MET amplifications were detected in 1.7% (10/590) of tumor tissue biopsies tested by both fluorescence in situ hybridization and sequencing in the pretreatment cohort [68]. In contrast, an NGS panel detected MET amplification in the ctDNAs of 22.6% (12/53) of patients who had been treated with anti-EGFR therapy and showed disease progression, which was not detected in patients with pre-cetuximab treatment.…”
Section: Met Amplificationmentioning
confidence: 99%